Principles of Freirean Didactics: subsidies for a didactic-pedagogical practice in higher education - Abensur, Patricia Lima Dubeux (2021)
This study presents a rereading of Paulo Freire's thought, concerning the teaching-learning process, with the objective of contributing to the didactics studies. It integrates a research, whose objective was to investigate the possibilities and the limits of building and experiencing a didactic-pedagogical practice subsidized by the Freirean principles. The theoretical framework is based on a Freire conceptual framework that takes the category teaching-learning as central and defines as essential, for this study, the relationship with the concepts of participation, dialogue, thematic research, knowledge and "Being More". The qualitative approach was adopted. The research proposal was materialized in the course “Didactic-Pedagogical Training in Health”, developed in ten classes, with thirty-one postgraduate students of strito sensu health courses at the São Paulo campus of the Federal University of São Paulo. In the production of data were used open and closed questionnaire, class audio, written activities developed during the course and field diary. The reading and analysis of the data showed the importance of the need to create concrete conditions for the discussion and reflection on aspects of the students' professional context; and, the recognition of the collective dimension in the construction of individual knowledge.